UJI MIKROPLAT AKTIVITAS ENZIM ESTERASE UNTUK MENDETEKSI RESISTENSI ANOPHELES ACONITUS TERHADAP INSEKTISIDA ORGANOFOSFAT - Widiarti, Widiarti (Lembaga Penelitian Universitas YARSI, 2005)
Non specific esterase are known to be important detoxification enzyme contributing to development of insecticides resistance in mosquitoes. Elevated esterase activity is one of the mechanisms of resistance to organophosphate, carbamate and pyrethroid insecticides in the mosquitoes. Such metabolic resistance can be detected by a microplate assay method. Mosquitoes vector resistance can occurs as a result of continuous exposure to the insecticide. Organophosphate insecticide has been used in the vector control program on Anopheles. aconitus, the malaria vector in Jepara Regency since 1983. The use of organophosphate and carbamate insecticides for five years for controlling Anopheles nigerrimus in Srilanka contribute to the selective resistance. This could happen to the population of An. aconitus in Jepara Regency. The objectives of this studies was to determine the potency of An. aconitus from Jepara Regency to be resistant to organophosphate insecticide related to esterase activity mechanism. The study methods used was biochemical assays (microplate assays )for elevated esterase. The level of esterases in larvae was determined using a and b naphthyl acetate, as the substrate andFast Blue B as the coupling reagent. The esterase activity was measured at 450 nm with Dytech ELISA plate reader. Microplate assay (Biochemical assays) on individual An. aconitus from Mlonggo II and Bangsri III subdistrics revealed that 12,9% and 28,6% population was resistant to organophosphate insecticide. The result showed that there was significant difference of elevated of esterase activity with both a and b naphthylacetate substrate hydrolysis, which appeared to be the major resistance mechanism in this multiple organophosphate resistant strain. Therefore the use of another insecticide group for vector control (An. aconitus) was suggested.